Relevansi Prinsip Ekonomi Islam dalam Pembinaan Umat Islam Indonesia - Mu'min Rauf (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
This article starts from a paradox in the economic conditionsthat occurred in Indonesia. On the one hand, Indonesia has most all natural resources (the SDA) which is relied upon by a number of countries. However, it can not be used to create prosperity. This article hypotizes that capitalism system is one of the reason. Therefore, it needs one system as a solution. This article concerns that Islamic economy supposed to be in both capitalism and socialism. This concept is appropiate for indonesia.DOI: 10.15408/aiq.v3i1.2517